Evaluating the effect of amalgam fillings on caries detection in cone-beam computed tomography images - Mehrdad Abdinian; Mohammad Amin Tavakoli Hranadi; Mohammad Hossein Manouchehri Naeini (Wolters Kluwer Medknow Publications, 2024)
Background: Dental caries stands as one of the most prevalent dental concerns, with early diagnosis being pivotal in clinical dentistry. Cone-beam computed tomography (CBCT) emerges as a widely utilized modality for dental caries identification, owing to its significant advantages. However, there remains a considerable knowledge gap regarding the efficacy of CBCT scans in detecting dental caries. In line with the as low as reasonably achievable principle, this study endeavors to evaluate the impact of amalgam fillings on the precision of occlusal caries detection in CBCT. Materials and Methods This in vitro study employed a set of 102 extracted human teeth samples. Among these, six molar teeth were used to create mesial-occlusal-distal amalgam restorations. The remaining teeth were placed in the dental sockets of a dry human skull to restore proximal contacts. CBCT images were obtained and examined by two observers, while histopathological examination was conducted using a stereomicroscope. Comparative analysis of CBCT images and histopathological data was performed using the McNemar test in SPSS software (α = 0.05). Results: The McNemar test results indicated that the nonrestoration group showed greater sensitivity and lower specificity in CBCT imaging than the amalgam-restored tooth group. Conclusion: The findings suggested that the CBCT technique did not demonstrate effectiveness in diagnosing dental caries around amalgam restorations.